Transmissible Endoplasmic Reticulum Stress: A Novel Perspective on Tumor Immunity - Jiang, Zhou; Zhang, Geru; Huang, Liwei; Yuan, Yihang; Wu, Chenzhou; Li, Yi (Frontiers in Cell and Developmental Biology, 2020)
As the first compartment of the protein secretory pathway, the endoplasmic reticulum (ER) acts as a protein synthesis factory, maintaining proteostasis and ER homeostasis. However, a variety of intrinsic and extrinsic perturbations, such as cancer, can disrupt the homeostasis and result in a large accumulation of misfolded/unfolded proteins in the ER lumen, thereby provoking a specific cellular state addressed as “ER stress”. Then the unfolded protein response (UPR), an adaptive signaling pathway, is triggered to address the stress and restore the homeostasis. A novel aspect of ER stress is that it can be transmitted from cancer cells to tumor-infiltrating myeloid cells through certain cancer cell-released soluble factors, which is termed as transmissible ER stress (TERS) or ER stress resonance (ERSR). In this review, we provide a comprehensive overview of the link between cancer and ER stress as well as the possible soluble factors mediating TERS. We further elaborate on the cell-extrinsic effects of TERS on tumor immunity, and how it indirectly modulates cancer development and progression, which is expected to add a new dimension to anticancer therapy.